Cardiac pauses during sleep in a patient with sleep obstructive apnea and atrial fibrillation. Issue 2 (October 2018) - Junqueiro, Isabel G.; Araújo, Paulo M.; Nunes, Alzira; Quinaz, João; Souteiro, Delfim; Campelo, Manuel; Drummond, Marta; Nunes, José Pedro L.
Abstract : Abstract: Cardiac rhythm disturbances are common in sleep apnea patients. The authors report on a 74-year-old female patient with atrial fibrillation, with a background history of arterial hypertension, obesity, and obstructive sleep apnea. Holter monitoring was performed, on 5 different occasions. Pauses were seen in every Holter monitoring, the number of which varied between 10 and 72. All pauses occurred during the sleeping period and adjacent hours (23:00–8:59 hours) with a single exception. In this patient, we can speculate that parasympathetic may predominate over sympathetic activity during sleep.